2009
DOI: 10.1111/j.1751-1097.2009.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arg123 in Light‐driven Anion Pump Mechanisms of pharaonis Halorhodopsin

Abstract: Halorhodopsin (HR) acts as a light-driven chloride pump which transports a chloride ion from the extracellular (EC) to the cytoplasmic space during a photocycle reaction that includes some photointermediates initiated by illumination. To understand the chloride uptake mechanisms, we focused on a basic residue Arg123 of HR from Natronomonas pharaonis (NpHR), which is the only basic residue located in the EC half ion channel. By the measurements of the visible absorption spectra in the dark and the light-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Since the water distribution around Glu234 is largely altered, it is likely that the pK a value of Glu234 is changed by the purple-to-blue transition. Diffraction data of the chloride-free blue or yellow form at various pH levels (pH [4][5][6][7][8][9][10] showed that the conformation of Glu234 remained unaltered in the investigated pH range. This observation suggests that Glu234 is deprotonated in the blue form and in the yellow form.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since the water distribution around Glu234 is largely altered, it is likely that the pK a value of Glu234 is changed by the purple-to-blue transition. Diffraction data of the chloride-free blue or yellow form at various pH levels (pH [4][5][6][7][8][9][10] showed that the conformation of Glu234 remained unaltered in the investigated pH range. This observation suggests that Glu234 is deprotonated in the blue form and in the yellow form.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4][5][6] HR is structurally similar to bacteriorhodopsin (BR), a light-driven proton pump found in Halobacterium salinarum. 7,8 Both HR and BR are made up of seven transmembrane helices (helix A through G) and the retinal chromophore that is bound via a protonated Schiff base to the ɛ-amino group of a lysine residue located in the middle of helix G. 9 In these retinylidene proteins, the photoisomerization of retinal around the C13 = C14 double bond triggers a series of conformational changes by which a proton or a chloride ion is transported.…”
Section: Introductionmentioning
confidence: 99%
“…Overall architectures viewed parallel to the membrane. Asn-98 in NM-R3) for Cl Ϫ transport (32)(33)(34). In addition, it was proposed that Asp-116 in KR2 (corresponding to Thr-102 in NM-R3) plays an important role in Na ϩ pumping, as estimated from the structure and mutant experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of R123 for HR function is highlighted by its conservation in all microbial-type rhodopsins [17], and by site-directed mutagenesis experiments indicating that the R123Q and R123H mutations abolish ion translocation [18]. The observation that even the conservative mutation R123K increases significantly the dissociation constant [18] suggests that not only the positive charge, but also the hydrogen bonding pattern is important for controlling the location of the chloride ion. To understand how R123 helps control chloride binding and translocation by halorhodopsins, we performed extensive all-atom molecular dynamics simulations on wild-type and three R123 mutants of pHR.…”
Section: Introductionmentioning
confidence: 99%